MULTIPLE PERSONALITY DISORDER OF Dr. JANG CHOEL IN PARTNERS FOR JUSTICE SEASON 2 MOVIE - RIZKY MIRANI DESI PRATAMA; Wiruma Titian Adi (LPPM Universitas Bina Sarana Informatika, 2019)
The objective of this research is to find out how multiple personality of dr. Jang Choel shown in Partners for Justice Movie Season 2 and the cause of the multiple personality disorder. This research uses descriptive qualitative method and library research. The writers found out that the real personality of dr. Jang is kind a warm person, but he will show his other personality which is dr.K if he remembers his childhood traumatic. The cause of his multiple personality disorder is physical abuse that performed by his mother. He also experienced traumatic of closed and dark place because he always locked by his mother in the bathroom when he made a mistake.